The Academic History of Literature and Art as a " Disease of Interpretation": On the Paradoxical Nature of Interdisciplinary Boundaries. (2nd July 2016) - Polonsky, Vadim
Abstract: This article represents an academic response to Professor Zhang Jiang's article "On Imposed Interpretation" published in Russian in the journal October (no. 1, 2015). It argues that the problems observed by Zhang arise from the reality of Western literary criticism over the past decades, and are associated with the contention between philosophy and philology that had its orgins in the West's Platonic heritage. In outlining the complex symbiotic relationship between the two disciplines in Western literary history, this article finds that two theoretical motive forces catalyzed the process: the "philologization of philosophy" and the "philosophization of philology." The writer argues that based on a full understanding of the paradoxical relationship between philosophy and philology, which are distinct from and yet attracted to each other, contemporary literary criticism can adopt the principles of "practical conservatism" and "cutting back of methodologies" as a means of healing the ever worsening "disease of intepreretation" in literary history.